Sarcopenia prevalence and association with nutritional status in cohort of elderly patients affected by musculoskeletal concerns: a real-life analysis - Maccarone, Maria Chiara; Coraci, Daniele; Bernini, Andrea; Sarandria, Nicola; Valente, Marta Rossella; Frigo, Anna Chiara; Dionyssiotis, Yannis; Masiero, Stefano (Frontiers in Endocrinology, 2023)
Introduction The progressive loss of skeletal muscle mass, strength, and function that frequently occurs as people get older is referred to as sarcopenia. Elderly musculoskeletal aging, sarcopenia, and obesity are all intimately connected. Our study's aim is to investigate the prevalence of sarcopenia in a real cohort of patients over 65 with musculoskeletal conditions referring to a Rehabilitation Unit. The secondary aim of our study is to investigate associations between sarcopenia and alterations in nutritional status and Body Mass Index (BMI). Finally, quality of life and global health has been investigated in our population. Materials and Methods From January 2019 to January 2021, 247 patients over 65 years old with musculoskeletal concerns were enrolled and participated in an observational study. As outcome measures, the Mini Nutritional Assessment (MNA), the 12-Item Short Form Health Survey (SF-12), and the Cumulative Illness Rating Scale Severity Index (CIRS-SI) were used. Additionally, measurements of total skeletal muscle mass (SMM) and appendicular muscle mass (ASMM) using bioelectrical impedance analysis, as well as a hand grip strength test of the non-dominant hand were taken. The Mid Upper Arm Circumference (MUAC) and the Calf Circumference (CC) were measured and recorded as further indications of possible sarcopenia. Results A percentage of 46.1% of subjects with overt sarcopenia was found and 10.1% showed a severe sarcopenia. Patients with severe sarcopenia showed significantly lower values of BMI and MNA. Additionally, sarcopenic patients showed significantly lower values in MNA when compared to non-sarcopenic patients. Considering SF-12, only the physical score revealed slight significant differences. In particular, patients affected by probable or severe sarcopenia presented a lower value than non-sarcopenic patients. Concerning MUAC and CC, severe sarcopenic patients showed significant lower values for both the body parts. Conclusion Our study considers a cohort of real-life elderly subjects with musculoskeletal concerns and shows that these subjects are highly susceptible to sarcopenia. Therefore, rehabilitation for elderly patients with musculoskeletal concerns requires to be customized and multidisciplinary. Future research should further investigate these aspects in order to enable the early identification of sarcopenia and the formulation of customized rehabilitative programs.